PENDIDIKAN AGAMA DAN BUDAYA: TRADISI NGUNJENG TANDHE’ DAN NILAI MODERASI BERAGAMA (Studi di Kabupaten Sumenep Madura) - Zaitur Rahem (Fakultas Agama Islam Universitas Islam Madura, 2023)
The concept of religious moderation in a number of scientific studies has so far been elaborated on, including love between people, harmony, balance, justice, and other moderating potentials. Religious harmony in Sumenep district has been established for a long time. Good relations between followers of one religion and another are close and strong. Even this closeness has an effect on the awareness of the Madurese people to be flexible in marrying culture and religious practice. One of them is integrating local culture in miniature practices that are full of Islamic religious teachings. As is the custom of nunjeng tanhe' on the wedding day. The focus of this research is: first, since when did tandhe' customs become an integral part of the practice of religious teachings. Second, what is the background of the people, Ngunjeng Tandhe' as entertainment in Walimatu al-Ursy? Third, what is the form of anti-radicalism education teachings in the ngunjeng tandhe culture and the link between Islam and the local culture? Fourth, what is the positive impact of the struggle between religion and local culture on the religious life of the community in the context of the local community? This research uses a qualitative approach with a type of field research. The object under study is the ngunjeng tandhe' tradition which is carried out by a number of residents in the Sumenep Madura district. The author collects data through documentation studies, interviews and observations. The data collected by the author analyzes well and systematically.